Analysis of Mathematical Literacy of Elementary School Teacher Candidates Using Ethnomathematics-Based Story Questions - Ema Butsi Prihastari; Budi Waluya; Nuriana Rachmani Dewi (Universitas Negeri Semarang, 2022)
This study aims to: 1) analyze the Mathematical literacy of prospective elementary school teachers using ethnomathematics-based story questions and 2) determine the role of ethnomathematics-based story questions in improving mathematical literacy. The research methods used are descriptive qualitative approaches-the research at one private university in Surakarta’s PGSD study program. The subjects used by students in the first semester of the 2022/2023 Academic Year were 32 students who took Geometry and Measurement courses. Sampling technique with purposive sampling analyses high, medium, and low-ability categories. Data collection techniques with interviews, documentation, and ethnomathematics-based story questions. The validity of the data uses triangulation of techniques and timing. Cycle model data analysis: 1) data reduction, 2) data presentation, and 3) conclusion drawing. The results; 1) the High category has Mathematical literacy ability at levels 4 to 6, the Medium category is at level 5, and the Low category is at levels 2 to 4. 2) the results of descriptive analysis state that ethnomathematics stories effectively increasing the Mathematical literacy of prospective elementary school teachers.